Progress and Controversy in Britain - Groombridge, Brian (International Review of Community Development / Revue internationale d’action communautaire)

(untitled) (Lien social et Politiques, 1980)
The author presents a debate in which he and Sir Kenneth Barrill, chairman of a British Think Tank closely linked to government circles, discuss priorities in Adult Education. While Sir Kenneth argues forcefully to direct government priorities towards job retraining programmes, Mr. Groombridge favours a more all-encompassing education policy that can answer human needs other than job qualification.